Modern views about reproductive health and potential in women with HIV infection and viral blood-borne hepatitis - E. V. Timofeyeva; O. Y. Leshchenko (Acta Biomedica Scientifica, 2014)
The article presents a review of literature devoted to the epidemiology of HIV infection in the world and Russia, as well as the investigation of reproductive disorders in women with HIV infection and viral blood-borne hepatitis. Actuality of the problem lies in the fact that grows the number of HIV infected and having blood-borne viral hepatitis with involvement in the epidemiological process people of reproductive age, and especially the increase in the number of HIV-infected women of childbearing age. Importantly, it is necessary to predict, diagnose and correct reproductive disorders in women, taking into account basic patterns and risk factors for the formation of such violations with a view to the restoration and preservation of reproductive capacity and ability to have healthy children.